Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Turn the equation into factored form
Y=x^3+3x^3-6x-8


Sagot :

y = x³ + 3x² - 6x - 8, to get the factored form put y = 0,
x³ + 3x² - 6x - 8 = 0, x³ + x² + 2x² + 2x - 8x - 8 = 0, 
x²(x + 1) + 2x(x + 1) - 8(x + 1) = 0,
(x + 1)(x² + 2x - 8) = 0, (x + 1)(x² + 4x - 2x -8) = 0, 
(x + 1)(x[x + 4] - 2[x +4]) = 0, 
(x +1)(x +4)(x - 2) = 0, this is the factored form.
x = -1, -4, 2.